Land‐use change trajectories up to 2050: insights from a global agro‐economic model comparison. (10th December 2013) - Schmitz, Christoph; van Meijl, Hans; Kyle, Page; Nelson, Gerald C.; Fujimori, Shinichiro; Gurgel, Angelo; Havlik, Petr; Heyhoe, Edwina; d'Croz, Daniel Mason; Popp, Alexander; Sands, Ron; Tabeau, Andrzej; et al.
Abstract Changes in agricultural land use have important implications for environmental services. Previous studies of agricultural land‐use futures have been published indicating large uncertainty due to different model assumptions and methodologies. In this article we present a first comprehensive comparison of global agro‐economic models that have harmonized drivers of population, GDP, and biophysical yields. The comparison allows us to ask two research questions: (1) How much cropland will be used under different socioeconomic and climate change scenarios? (2) How can differences in model results be explained? The comparison includes four partial and six general equilibrium models that differ in how they model land supply and amount of potentially available land. We analyze results of two different socioeconomic scenarios and three climate scenarios (one with constant climate). Most models (7 out of 10) project an increase of cropland of 10–25% by 2050 compared to 2005 (under constant climate), but one model projects a decrease. Pasture land expands in some models, which increase the treat on natural vegetation further. Across all models most of the cropland expansion takes place in South America and sub‐Saharan Africa. In general, the strongest differences in model results are related to differences in the costs of land expansion, the endogenous productivity responses, and the assumptions about potential cropland.